FEASIBILITY OF SUSTAINABLE DEVELOPMENT BY CLOUD COMPUTING IN ASEAN REGION - Tehrani, Pardis Moslemzadeh (UI Scholars Hub, 2016)
One of the most vital societal challenges of the 21st century is sustainable development.The rapid development and application of information technology (IT) is a global trend with significant implications for sustainable development. According to the findings of global action plan, electronic devices such as computers, laptops, and mobile devices account for 2% of greenhouse gas emissions worldwide. This figure cannot be reduced without effortsfromcompanies that support the “green IT” concept. Long-lasting products with low-energy consumption can save energy. However, green IT products have no international label. Even thoughseveral companies have developed certain labels, monitoring their quality remains difficult, and a guideline for quality checking is needed. Cloud storage is one of the methodsthat can reduce energy consumption. The main goal of the ASEAN community is to leverage on sustainable development in the ASEAN region through enhancing cooperation among member states in different aspects of life. In doing so, the ASEAN attempts to facilitate information exchange among member states which would be facilitatedby cloud storage. Therefore, creating a policy guideline is necessary to enable member states to mandate the use of large computing centers for companies to ensuresustainable energy savings. Companies typically use old servers that consume a significant amount of energy inefficiently. Thus, they need to set up fewer servers with highly efficient output.The purpose of this study is to consider the relationship between cloud computing and sustainability within the ASEAN region and to formulate a suitable legal framework for promoting cloud computing it amongmember states. This paper also aims to examine how ASEAN can encourage member states to utilize the cloud computing technology through legal frameworks thatare intended to reduce power consumption in the information and communication technology departments of various organizations.